Pedagogic Techniques for Forming Professional Readiness of the Future Technology Teachers - Oleksandr Livshun (Pedagogical Discourse, 2013)
The article reviews meanings of such notions as «technology», «pedagogic techniques» in the education process, analyzes main components of the technique, reveals kinds of techniques for different types of activity. The acmeologic approach to the formation of professional readiness of Technology teachers to be is studied. The author focuses on the efficiency of profession-oriented modules of acmeologic trainings and acmeologic developmental classes. The content, technological and organizational structures of the training modules are studied.